2015
DOI: 10.1142/s0219887815500188
|View full text |Cite
|
Sign up to set email alerts
|

Super-Lie n-algebra extensions, higher WZW models and super-p-branes with tensor multiplet fields

Abstract: We formalize higher-dimensional and higher gauge WZW-type sigma-model local prequantum field theory, and discuss its rationalized/perturbative description in (super-)Lie n-algebra homotopy theory (the true home of the “FDA”-language used in the\ud supergravity literature). We show generally how the intersection laws for such higher WZW-type σ-model branes (open brane ending on background brane) are encoded precisely in (super-)L∞-extension theory and how the resulting “extended (super-)spacetimes”\ud formalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(107 citation statements)
references
References 51 publications
1
106
0
Order By: Relevance
“…Rather, in general it is only locally so, but is globally a (p + 1)-form connection on a "(p + 1)-bundle" or "p-gerbe". This is notably the case for field theories of Wess-Zumino-Witten type; see [21] for review of this fact and for pointers to the literature.…”
Section: Poisson Bracket Lie N-algebrasmentioning
confidence: 95%
See 4 more Smart Citations
“…Rather, in general it is only locally so, but is globally a (p + 1)-form connection on a "(p + 1)-bundle" or "p-gerbe". This is notably the case for field theories of Wess-Zumino-Witten type; see [21] for review of this fact and for pointers to the literature.…”
Section: Poisson Bracket Lie N-algebrasmentioning
confidence: 95%
“…Now the proper global analysis of [2, p. 8] and of proposition 5.2 only ever produces extensions by charges of a single brane species with no (higher) gauge fields on its worldvolume. But in [21,22,39] we explained that the WZW-type sigma models for super p 2 -branes with (higher) gauge fields on the their worldvolume and on which super p 1 -branes may end, are globally defined not on target superspacetime X itself, but on the total space X of a super p 1 -stack extension X → X of superspacetime, which itself is a differential refinement of the p 1 -gerbeX that underlies the WZW term of the p 1 -branes. Moreover, in [16] we showed that the higher Heisenberg-Kostant-Souriau extensions of remark 2.11 generalizes to such higher stacky base spaces.…”
Section: Application To Brane Chargesmentioning
confidence: 99%
See 3 more Smart Citations